A microRNA expression signature for the prognosis of oropharyngeal squamous cell carcinoma. Issue 1 (26th June 2012) - Gao, Ge; Gay, Hiram A.; Chernock, Rebecca D.; Zhang, Tian R.; Luo, Jingqin; Thorstad, Wade L.; Lewis, James S.; Wang, Xiaowei
Abstract BACKGROUND: Oropharyngeal squamous cell carcinoma (SCC) rates have been increasing significantly in recent years, despite a decreasing incidence of head and neck cancer in general. Oropharyngeal SCC has many characteristics that are distinct from other head and neck cancers, and thus it is important to focus specifically on cancers arising in this region, with the goal of improving patient outcomes. One important goal is to identify those patients who are likely to fail standard therapy and who could potentially benefit from alternative or targeted treatments. METHODS: In the current study, the prognostic value of microRNAs (miRNAs) was evaluated in patients with oropharyngeal SCC. miRNAs are small, noncoding RNAs that are master regulators of many important biological processes. In total, 150 oropharyngeal tumors were analyzed using the recently developed quantitative polymerase chain reaction‐based method for miRNA expression profiling. In addition, the expression of miRNAs was also compared with human papillomavirus (HPV) transcriptional activities. RESULTS: The current study identified 6 miRNAs that were found to be significantly associated with cancer survival. A combined expression signature of these miRNAs was prognostic of oropharyngeal SCC, independent of common clinical features or HPV status. CONCLUSIONS: This new miRNA signature was experimentally validated in an independent oropharyngeal SCC cohort. Furthermore, 5 HPV‐related miRNAs were identified, which may help to characterize HPV‐induced cancers including both oropharyngeal and cervical SCC. Cancer 2013. © 2012 American Cancer Society.